Feminisme Liberal dalam Anime Kidō Senshi Gandamu Tekketsu No Orufenzu Karya Tatsuyuki Nagai - Putra, I Made Dwi Christian Gustiana (KIRYOKU, 2021)
This research is entitled "Liberal Feminism in Kidō Senshi Gandamu Tekketsu no Orufenzu Anime by Tatsuyuki Nagai". Purpose of this this research of this study is to determine the form of liberal feminism from the main female character and the existence of female characters in Kidō Senshi Gandamu Tekketsu no Orufenzu Anime. In analysis, the theories used in this research are liberal feminism theory by Tong and sociology of literature by Wellek and Werren. Based on the analysis results, it was found that the liberal feminism that appears in the anime Kidō Senshi Gandamu Tekketsu No Orufenzu contained in the Kudelia character is the image of women, the position of women, intellectual women, and women who have a high degree of curiosity. Efforts to enforce the existence of women are seen from the existence of female characters.